Adult learning, situated cognition, and authentic activity: Relocating adult education in the context of experience - Arthur L. Wilson (Adult Education Research Conference, 1993)
The purpose of this paper is to situate adult learning as a complex social phenomenon in which people, setting, and culturally-provided tools contribute essential elements to adult cognition.